Catalytic and Enantioselective Control of the C–N Stereogenic Axis via the Pictet–Spengler Reaction. (23rd April 2021) - Kim, Ahreum; Kim, Aram; Park, Sunjung; Kim, Sangji; Jo, Hongil; Ok, Kang Min; Lee, Sang Kook; Song, Jayoung; Kwon, Yongseok
Abstract: An unprecedented example of a chiral phosphoric acid‐catalyzed atroposelective Pictet–Spengler reaction of N ‐arylindoles is reported. Highly enantioenriched N ‐aryl‐tetrahydro‐β‐carbolines with C−N bond axial chirality are obtained via dynamic kinetic resolution. The hydrogen bond donor introduced on the bottom aromatic ring, forming a secondary interaction with the phosphoryl oxygen, is essential to achieving high enantioselectivity. A wide variety of substituents are tolerable with this transformation to provide up to 98 % ee . The application of electron‐withdrawing group‐substituted benzaldehydes enables the control of both axial and point stereogenicity. Biological evaluation of this new and unique scaffold shows promising antiproliferative activity and emphasizes the significance of atroposelective synthesis. Abstract : Catalytic and enantioselective control of the C–N stereogenic axis of heterocyclic scaffolds is reported. The asymmetric Pictet–Spengler reaction is achieved by employing a chiral phosphoric acid via dynamic kinetic resolution. Application to substituted benzaldehyde enables control of both axial and point chirality.